Wissensbearbeitung im Produktionsprozess des zeitgenössischen Dokumentartheaters (Studia theodisca, 2016)
Documentary theatre aims to portray truth or authenticity. It tries to produce knowledge, though it is rather difficult to assert the authenticity of this knowledge because the sources imply a great deal of subjectivity. It is a medium that asks questions about how to pass on knowledge not only through the body and the voice, but also through the meeting of multiple people and the exchange between the stage and the audience. This study will analyse, through several contemporary documentary plays, how knowledge, and of what kind, can be produced on stage and if there is a particular aesthetics for this production.